Stone Monuments of Islam: Cultural Leaps and Acculturation at Ulak Lebar Lubuklinggau - Yadri Irwansyah; Muhammad Abdul Karim; Maharsi Maharsi (UIN Sunan Gunung Djati, 2025)
Religion and culture are two elements that constantly interact in shaping human civilisation, including in the context of Indonesian local culture. The megalithic site of Ulak Lebar in Lubuklinggau City is one cultural heritage site that shows traces of the encounter between local traditions and Islamic influences. This article aims to reveal the process of socio-cultural change that occurred through the interaction between megalithic traditions and Islamic teachings at the site. This study uses historical methods through the stages of heuristics, source criticism, interpretation, and historiography. The results of the study indicate that there has been a balanced cultural acculturation between megalithic and Islamic cultures, resulting in a unique cultural product in the form of Islamic menhirs paired menhirs used as grave markers. This finding indicates a cultural leap, in which Hindu-Buddhist culture, which generally served as a transitional phase in other regions, did not play a significant role in Ulak Lebar. This acculturation occurred because the megalithic tradition was deeply rooted in the community, while Islam arrived through an inclusive approach to power via the Sultanate of Palembang. This research contributes to the study of local cultural history, particularly in understanding the dynamics of cultural integration in the inland regions of South Sumatra, and underscores the importance of preserving cultural heritage in the context of social change.